Analisis Nilai Kalor Pada Empat Sisi Dinding Kompor Biomassa - Muh Firdan Nurdin; Hadi Santoso; Masbin Dahlan (Journal of Energy, Materials, & Manufacturing Technology, 2023)
Biomass stove is one of the technologies for utilizing biomass for cooking purposes in the household sector. The commonly used biomass in biomass stoves is meranti wood which is used as fuel in this study. This study aims to analyze the heatloss on the sides of the biomass stove (left, right, front and rear). Tests were carried out using three water volume variations about 1 liter, 1.5 liter and 2 liter. The results of this study indicate that the maximum heat is 16.2 kCal on the front side of the stove for a 2 liter water volume, while the minimum heat is 5.8 kCal on the back side of the stove for 1 liter water volume.